MySurf Technology Inventory Management System - Ameran, Farra Aliesya; Mohamad, Radiah (Applied Information Technology And Computer Science, 2025)
The use of digital recording technology has become important for operational optimisation in a variety of sectors. MySurf Technology, a computer accessories store, is currently dealing with inventory management inefficiencies as a result of its reliance on obsolete manual recording systems, particularly those centred on Microsoft Excel. This reliance on previous methods causes inconsistencies in inventory counts and takes a significant amount of time for detailed calculations. To address these ongoing issues, a sophisticated inventory management system created for MySurf Technology is being developed. This system aims to improve inventory management, improve sales reporting, and reduce mistakes common in manual record-keeping techniques. Using a prototype model for system development enables for early user involvement, allowing for a better understanding of the system’s functionality and the early detection of any errors. Upon completion, this system shall be able to maintain MySurf’s inventory information systematically, allowing for quick data access and retrieval. This technical innovation is expected to improve operational efficiency, enabling data-driven decision-making, and enhance customer service standards, ensuring MySurf’s competitiveness in today’s market environment.